Research on Cumulative Damage Characteristics of Rock Anchor Beam Concrete Supporting Structure by Blasting Vibration of Underground Powerhouse - Sheng Wan; Junhong Huang; Yi Luo; Xinping Li; Qingsong Pu (Shock and Vibration)
Aiming at the dynamic disturbance problem of the upper rock anchor beam concrete support structure caused by the blasting excavation of the lower rock mass of the underground powerhouse of the hydropower station, the dynamic finite element software was used to numerically simulate the cumulative damage characteristics of the rock anchor beam concrete structure under multiple blasting, which aims to study the effect of blasting times and blast center distance on the cumulative damage characteristics of rock anchor beam concrete structures in two directions at different ages. The results show that 7 days after the completion of the concrete pouring of rock anchor beam, the damage and destruction effects are produced under the single blasting action. 28 days after the completion of the concrete pouring, there is basically no damage and destruction under the action of five times of blasting. 14 days after the completion of the concrete pouring, the growth process of the cumulative damage effect of the rock anchor beam concrete structure under the disturbance of the blasting excavation of the underground powerhouse shows nonlinear increasing characteristics with the increase of blasting times and nonlinear decreasing characteristics with the increase of blasting center distance. The cumulative damage of rock anchor beam along and perpendicular to the axis of powerhouse conforms to the relationship of cubic polynomials with the blasting times, which also conform to the relationship of quartic polynomial and quadratic polynomial, respectively, with the blast center distance.